An Investigation of the Relationship between Academic Buoyancy and Academic Performance among Senior High School Students: A Quantitative Research Approach (International Journal of Metaverse, 2023)
Academic buoyancy is a student’s ability to effectively deal with academic setbacks and challenges. This study aimed to determine whether academic buoyancy predicts academic performance among high school students. The objective of this study was to investigate the relationship between academic buoyancy and academic performance among high school students. Participants were 142 high school students who completed a questionnaire that included measures of academic buoyancy and grade point average (GPA). Data were analyzed using simple linear regression and frequency distribution. The results showed that academic buoyancy predicted academic performance among high school students. About 11.6% of the variation in academic performance was explained by academic buoyancy. The average GPA of the participants was 86.51, and the average academic buoyancy score was 4.69. The findings suggest that academic buoyancy is a valuable predictor of academic performance among high school students. Teachers and educators can use this knowledge to help students develop their academic buoyancy and improve their academic performance.